The Bad Beginning - Snicket, Lemony; Illustrated by Helquist, Brett (London Modern Classics, 2016)
`If you are interested in stories with happy endings, you would be better off reading some other book.'Violet, Klaus and Sunny Baudelaire are most unfortunate children. Orphaned after the sudden death of their parents in a house fire, they are left in the hands of their guardian, Count Olaf, who has diabolical plans for them . . .
Include Illustrations
Keywords: Humorous stories -- Humorous stories, English